Edycja XIV- i XV-wiecznych poznańskich ksiąg ziemskich. Transliteracja = Edition of the 14th and 15th centuries of Poznan Land Book. Transliteration - Trawińska, Maria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article discusses the difficulties of transliteration of earth books, which are inscribed in gothic italics. This script is characterized by a large variant of graphics, numerous abstractions and ligatures. These features make it very difficult to identify multiple letters and often cause graphs to come through semantics, that is, first determine the meaning of the reading, then indicate its graphical value.
Keywords: średniowieczne rękopisy; kursywa gotycka; edycja; transliteracja; medieval manuscripts; italic gothic; edition; transliteration